Chimaphila umbellata extract exerts anti-proliferative effect on human breast cancer cells via RIP1K/RIP3K-mediated necroptosis - Neeladrisingha Das (Elsevier, 2022)
Background: Chimaphila umbellata (CU) is a small perennial plant whose roots and leaves are used in the preparation of homeopathic medicines. In this study, the anti-proliferative and apoptotic effects of CU extract, obtained from its homeopathic mother tincture, were evaluated in human breast cancer cell lines. Methods: MTT assay was used to evaluate the dose- and time-dependent cytotoxicity of the extract in MCF-7 and HEK293 cells. The anti-proliferative effect of the extract was evaluated using the clonogenic and wound healing assays. The anti-angiogenic activity of the drug was evaluated using the chick chorioallantoic membrane assay. The mode of cell death was analyzed using Annexin V and PI staining assays through flow cytometry. In addition, the expression patterns of associated genes were evaluated using immunoblot analysis. Results: CU extracts exerted anti-proliferative effect in breast cancer cell line, i.e., MCF-7 cells, by inhibiting their growth and migration. The extract also demonstrated significant anti-angiogenic ability, limiting the de-novo blood vessel growth and development in chick embryos. The extract was found to increase caspase-independent necroptosis by involving RIP1/RIP3 kinases and MLKL proteins. This finding was further confirmed by using NEC-1 (an inhibitor of necroptosis), which significantly abolished the CU extract-induced necroptotic effect. Conclusions: The CU extract exhibits great potential in preventing breast cancer and thus warrants further investigations in vivo.